Comet and cup genes in Drosophila spermatogenesis: the first demonstration of post-meiotic transcription. (21st May 2008) - Barreau, Carine; Benson, Elizabeth; White-Cooper, Helen
Abstract : Post-meiotic transcription is widespread in mammalian spermatogenesis, but is generally believed to be absent from Drosophila spermatogenesis. Genes required during meiosis, in early spermatids or later in spermiogenesis are typically transcribed in primary spermatocytes in Drosophila . Their mRNAs are then stored in the cytoplasm until the protein product is needed. Recently, using in situ hybridization, we identified 17 Drosophila genes, collectively named 'comets' and 'cups', whose mRNAs are most abundant in, and localize to the distal ends of, elongating spermatids. Using a single-cyst quantitative RT–PCR (reverse transcription–PCR) assay, we confirmed this unusual expression pattern and conclusively demonstrate the existence of post-meiotic transcription in Drosophila spermatids. We found that transcription of comets and cups occurs just before protamines can be detected in spermatid nuclei.